Emotions, affections, and psychopathy among female prisoners - Pinheiro, Marina (2020)
The present study intends to be a contribution to understand affections and emotions associated with female psychopathy. Although there are several studies aiming to understand psychopathy, there is still a gap in the integration of such a concept in affective dimensions, as well as a scarcity of surveys conducted in the female population. Sixty-three women confined to prison, located in the North region of Portugal, participated in this study. Participants were assessed using the Positive and Negative Affect Schedule (PANAS), the Levenson’s Self-Report Psychopathy Scale (LSRP), and the Hare’s Psychopathy Checklist–Revised (PCL-R). Results showed that only nine women presented moderate scores of psychopathy. Moreover, women with higher psychopathy scores revealed deficits in positive emotional abilities, and secondary psychopathy was related with predominance of negative affection. In the future, it would be useful to develop more effective instruments to assess emotions and affections in psychopaths.